2002
DOI: 10.1097/00007890-200201270-00008
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Histology for Monitoring Treatment of Acute Rejection in Pancreaticoduodenal Allografts in Rats1,2

Abstract: Duodenal histology accurately predicts the initial diagnosis of rejection of the pancreas. However, after treatment of acute rejection, duodenal morphology is more likely to recover from rejection than the pancreas. Awareness of this phenomenon might be important for the interpretation of duodenal follow-up biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The authors, however, found that morphologic changes readily respond to treatment in the duodenum but not in the pancreatic portion of the graft. Awareness for this phenomenon is important for the interpretation of duodenal biopsies after antirejection therapy (21). A pig model compared the degree of vascular and interstitial rejection of the duodenal and pancreatic part of the graft and revealed exact correlation between the pancreas and the duodenum in 47% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…The authors, however, found that morphologic changes readily respond to treatment in the duodenum but not in the pancreatic portion of the graft. Awareness for this phenomenon is important for the interpretation of duodenal biopsies after antirejection therapy (21). A pig model compared the degree of vascular and interstitial rejection of the duodenal and pancreatic part of the graft and revealed exact correlation between the pancreas and the duodenum in 47% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Every animal with histologically proven rejection of the pancreas also showed clear signs of rejection in the duodenum [35]. In a rat model of pancreas, transplantation duodenal histology had a positive and negative predictive value of 100% for the detection of acute rejection in the pancreatic portion of the graft [36]. When considering interstitial and vascular changes, vascular features correlated to a higher extent between the two portions of the graft than did interstitial features.…”
Section: Correlation Between Rejection Of the Duodenum And Rejection mentioning
confidence: 96%
“…Even when laparoscopic biopsy is performed the success rate is 90% (3). It was shown that the duodenal histology predicts the initial diagnosis of rejection of the pancreas, being less accurate for monitoring recovery from rejection (4). It was also reported that rejection process might occur independently in either organ (5).…”
mentioning
confidence: 99%